Comparative Evaluation of Seven Commercial Tests for Detection of Heterophile Antibody in Infectious Mononucleosis. (1992) - Skulnick, Martin; Low, Donald E; Simor, Andrew E; Patel, Mohan; George, Pauline; Chua, Robert
Abstract : Detection of heterophile antibodies in infectious mononucleosis is the most rapid and cost-effective method for confirming the clinical diagnosis of the disease. This study compared seven commercial test kits (the Oxoid Infectious Mononucleosis Kit [Oxoid Ltd], Immunoscan Im-Latex [Baxter Travenol], Mono-Latex [Wampole Laboratories], Monospot and Im Screen Test [Ortho Diagnostics], Immunoscan Im-RBC Test [Baxter Travenol], and Infectious Mononucleosis Test [NCS Diagnostics]) to the Davidsohn differential test. All of the kits were shown to be acceptable for use, with specificities and sensitivities greater than 96.5% and 95.5%, respectively.